2005
DOI: 10.1038/ncb1274
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-dependent localization of targeted mRNAs to mammalian P-bodies

Abstract: Small RNAs, including small interfering RNAs (siRNAs) and microRNAs (miRNAs) can silence target genes through several different effector mechanisms1. Whereas siRNA-directed mRNA cleavage is increasingly understood, the mechanisms by which miRNAs repress protein synthesis are obscure. Recent studies have revealed the existence of specific cytoplasmic foci, referred to herein as processing bodies (P-bodies), which contain untranslated mRNAs and can serve as sites of mRNA degradation2-7. Here we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
905
1
19

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,095 publications
(964 citation statements)
references
References 31 publications
39
905
1
19
Order By: Relevance
“…The human Ago proteins have 77.6 to 83.6% sequence identity with each other (Sasaki et al, 2003) and 4F9 most likely recognizes a shared conformational epitope found in all Ago proteins. In addition, it was previously reported that all 4 Ago proteins localized to GWBs (Liu et al, 2005b). Taken together, we concluded that 4F9 binds all Ago proteins.…”
Section: All Ago Proteins Could Be Recognized By 4f9supporting
confidence: 81%
See 1 more Smart Citation
“…The human Ago proteins have 77.6 to 83.6% sequence identity with each other (Sasaki et al, 2003) and 4F9 most likely recognizes a shared conformational epitope found in all Ago proteins. In addition, it was previously reported that all 4 Ago proteins localized to GWBs (Liu et al, 2005b). Taken together, we concluded that 4F9 binds all Ago proteins.…”
Section: All Ago Proteins Could Be Recognized By 4f9supporting
confidence: 81%
“…The key components of the RISC complex are Argonaute (Ago) proteins with molecular masses of approximately 100 kDa and containing PAZ and PIWI domains (Carmell et al, 2002;Sasaki et al, 2003). Four of these, Ago1 to Ago4, have been demonstrated to associate with miRNAs in humans (Liu et al, 2005b). However, only Ago2 has been demonstrated to possess the activity of miRNA-guided mRNA cleavage or translational inhibition .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AIN-1, the worm GW182 orthologue, interacts with DCR-1 suggesting that events before RISC assembly may take place in these structures (Ding et al, 2005;Meister et al, 2005). The RNA-and miRNA-independent interaction between hAgo2 and Dcp1a strengthens this hypothesis (Liu et al, 2005b).…”
Section: Mechanism(s) Of Mirna-mediated Gene Regulationmentioning
confidence: 72%
“…Within P-bodies, miRNA/ mRNA-bound argonaute protein recruits GW182 protein (TNRC6A), which subsequently recruits deadenylating enzyme CCR4-NOT1 (CNOT1), and this is followed by mRNA decapping by DCP1-DCP2 enzyme -thereby affecting stability of repressed mRNA. Repressed mRNAs are then degraded by 5 0 to 3 0 exonuclease activity of XRN1 (5 0 -exoribonuclease 1) (Refs 43,55,57,62,63) (Fig. 2c).…”
Section: Mechanism(s) Of Mirna Actionmentioning
confidence: 99%